2022
DOI: 10.3390/molecules27175561
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Quinacrine as a Potent Topo II and Hsp90 Dual-Target Inhibitor, Repurposing for Cancer Therapy

Abstract: Topo II and Hsp90 are promising targets. In this study, we first verified the structural similarities between Topo IIα ATPase and Hsp90α N−ATPase. Subsequently, 720 compounds from the Food and Drug Administration (FDA) drug library and kinase library were screened using the malachite green phosphate combination with the Topo II-mediated DNA relaxation and MTT assays. Subsequently, the antimalarial drug quinacrine was found to be a potential dual−target inhibitor of Topo II and Hsp90. Mechanistic studies showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Metformin, the widely used antidiabetic drug, exhibited anticancer and chemosensitization properties in preclinical and clinical studies [16,17]. The antimalarial drug quinacrine was found to be a dual target antiproliferative agent by inhibition of Topo II and Hsp90 [18]. In addition, quinacrine was repurposed for managing cancer by other several mechanisms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, the widely used antidiabetic drug, exhibited anticancer and chemosensitization properties in preclinical and clinical studies [16,17]. The antimalarial drug quinacrine was found to be a dual target antiproliferative agent by inhibition of Topo II and Hsp90 [18]. In addition, quinacrine was repurposed for managing cancer by other several mechanisms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The antimalarial drug quinacrine was found to be a dual target antiproliferative agent via the inhibition of Topo II and Hsp90 [ 18 ]. In addition, quinacrine was repurposed for managing cancer by several other mechanisms [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early observations showed conflicting findings on the antidepressants' effect on cancer promotion and growth [26,28]. Later studies revealed the great potential of antidepressant drugs, including tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs), for repurposing to cancer The antimalarial drug quinacrine was found to be a dual target antiproliferative agent via the inhibition of Topo II and Hsp90 [18]. In addition, quinacrine was repurposed for managing cancer by several other mechanisms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…phosphoserine phosphatase activity [17], library screenings for kinases [18] and, especially to measure primitive aminoacyl-tRNA synthetase (protozyme) activity [19]. We describe here the first adaptation of this assay into a simple, rapid, and sensitive zymography technique, with specific protocols, cognate amino acid-dependence, and insensitivity to phosphatase and kinase blockers, so that aaRS activities can be detected in both complex protein mixtures and purified samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this new method, Malachite green and hexaammonium heptamolybdate tetrahydrate greatly enhance the intensity of the coloured complex with orthophosphates generated from PPi above and adjacent to active aaRS proteins in the gel[15]. The Malachite green assay was previously used by several groups to study cyclic nucleotide phosphodiesterase activity[16], phosphoserine phosphatase activity[17], library screenings for kinases[18] and, especially to measure primitive aminoacyl-tRNA synthetase (protozyme) activity[19]. We describe here the first adaptation of this assay into a simple, rapid, and sensitive zymography technique, with specific protocols, cognate amino acid-dependence, and insensitivity to phosphatase and kinase blockers, so that aaRS activities can be detected in both complex protein mixtures and purified samples.…”
Section: Introductionmentioning
confidence: 99%